Ontology Editing Tools: A Comparative Perspective - Ramya, D; Kiran Kumar, V (International Journal of Computer Sciences and Engineering, 2025)
With the revolutionary advent of the Semantic Web and the corresponding technologies, Ontologies have lately gained tremendous patronage and popularity from a large cross-section of users from the realm of knowledge management. This paper seeks to make an insightful comparative analysis of a few select software tools, associated with ‘Semantic Web’. As a matter of fact, this study attempts an insightful comparative description of six ontology-editors, viz. Protégé, Swoop, Vitro and Fluent. Also, it describes the key structural aspects of the above editors, including its basic features, apart from the methods of use. In essence, convenience for the user as well as the multiple possibilities of applications is considered as the primary criterion for comparison among these editors. Diverse user groups prefer to use Ontology Building/Management tools while handling several tasks. Even though, each tool defines a specific functionality, many users prefer to use it only for a single purpose for migration within their host ontologies, from one tool to another. Additionally, we evaluated the compatibility among various ontologies by applying many development and management tools. Finally, it detects the many similarities and diversities found among the analyzed ontologies, both within a particular domain (application area) as well as with other domains.